The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1038/s41598-019-52895-y
|View full text |Cite
|
Sign up to set email alerts
|

Photonic integration based on a ferroelectric thin-film platform

Abstract: Photonic-integrated circuits (PICs) using ferroelectric materials are expected to be used in many applications because of its unique optical properties such as large electro-optic coefficients. In this study, a novel PIC based on a ferroelectric thin-film platform was designed and fabricated, where high-speed optical modulator, spot-size converters (SSCs), and a variable optical attenuator (VOA) were successfully integrated. A ferroelectric lanthanum-modified lead zirconate titanate (PLZT) thin film was epitax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Ferroelectricity in Rochelle salt was discovered in 1921 by J. Valasek [1], with the sign of spontaneous polarization (P s ) being controllable by an external electric field. Since this discovery, many efforts have been made to enhance technological applications, such as field-effect transistors (FeFET) [2], sensors [3], photonic devices [4], and optoelectronics [5]. However, the constant demand for higher-performance devices has necessitated increased efforts toward miniaturization in nanoelectronics, and consequently, toward the preparation of thin and ultra-thin ferroelectric films.…”
Section: Introductionmentioning
confidence: 99%
“…Ferroelectricity in Rochelle salt was discovered in 1921 by J. Valasek [1], with the sign of spontaneous polarization (P s ) being controllable by an external electric field. Since this discovery, many efforts have been made to enhance technological applications, such as field-effect transistors (FeFET) [2], sensors [3], photonic devices [4], and optoelectronics [5]. However, the constant demand for higher-performance devices has necessitated increased efforts toward miniaturization in nanoelectronics, and consequently, toward the preparation of thin and ultra-thin ferroelectric films.…”
Section: Introductionmentioning
confidence: 99%
“…The gray-scale photomask process needs costly photomask and experimental tuning of the geometry of the photomask. 30) In this study, we present a simple fabrication process of vertical-taper structure that is realized by a combination of our step-and-exposure lithography 31,32) and dry etching. The process can realize the precise control of the thickness and the angle of silicon waveguides without annealing at high temperatures or special processes.…”
Section: Introductionmentioning
confidence: 99%
“…34 In 2019, a prospect for future research, especially about ferroelectric thin film (e.g., PLZT) applied in optical interconnection devices, was reported by Abe who integrated optical modulator, spot-size converters (SSCs) and a variable optical attenuator on the PLZT thin film platform. 35 However, the PLZT films they developed only possess a linear EO effect. The EO effect of PLZT films is very different from that of PLZT ceramic, because the film thickness, the annealing temperature, and conditions will have great influence on the EO characteristics.…”
mentioning
confidence: 99%
“…Meanwhile, much research about PLZT thin films showed a huge linear EO effect, which is used in integrated nanophotonic devices . In 2019, a prospect for future research, especially about ferroelectric thin film (e.g., PLZT) applied in optical interconnection devices, was reported by Abe who integrated optical modulator, spot-size converters (SSCs) and a variable optical attenuator on the PLZT thin film platform . However, the PLZT films they developed only possess a linear EO effect.…”
mentioning
confidence: 99%